2021
DOI: 10.21203/rs.3.rs-668192/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Onsite versus remote working: the impact on satisfaction, productivity, and performance of medical call center workers

Abstract: Background Job satisfaction is determined as the measure to know the individuals’ feelings toward their work. The working conditions that can affect the call center agents’ satisfaction, and performance have received particular concern. Methods This study included 124 agents working in a governmental medical call center in Saudi Arabia. Each agent was receiving a questionnaire that investigates their satisfaction, productivity and performance during working in the medical call center. Results Seventy-seven … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Policymakers can promote the dissemination of best management practices, self-management skills and ICT, investment in home offices, and fast and reliable broadband across the country, to improve teleworking gains [ 48 ]. The results of Alfaleh et al's study [ 49 ] showed that doctors working in medical centers are primarily satisfied with teleworking in terms of job nature and productivity.…”
Section: Discussionmentioning
confidence: 99%
“…Policymakers can promote the dissemination of best management practices, self-management skills and ICT, investment in home offices, and fast and reliable broadband across the country, to improve teleworking gains [ 48 ]. The results of Alfaleh et al's study [ 49 ] showed that doctors working in medical centers are primarily satisfied with teleworking in terms of job nature and productivity.…”
Section: Discussionmentioning
confidence: 99%